THE QUEST FOR BRIDGING TRIFLUOROPHOSPHINE LIGANDS IN TRANSITION METAL COMPLEXES - KING, Robert Bruce (Studia Universitatis Babeș-Bolyai Chemia, 2016)
Trifluorophosphine is a strong back-bonding ligand like the ubiquitous carbonyl ligand. In fact mononuclear zerovalent trifluorophosphine complexes such as M(PF3)6 (M = Cr, Mo, W), M(PF3)5 (M = Fe, Ru), and M(PF3)4 (M = Ni, Pt) are even more stable than their well-known carbonyl analogues. However, metal complexes with bridging trifluorophosphine ligands are virtually unknown. We review theoretical studies on the Co2(PF3)8, Fe2(PF3)9, and Cp2Fe2(PF3)n (Cp = h5-C5H5; n = 4, 3) systems analogous to the well-known metal carbonyls Co2(CO)6(µ-CO)2, Fe2(CO)6(µ-CO)3, Cp2Fe2(CO)2(µ-CO)2, and Cp2Fe2(µ-CO)3 containing two or three bridging CO groups. In most cases structures having features other than bridging PF3 groups are energetically preferred.